Dancing with passion: A look at interpersonal relationships. (May 2020) - Guilbault, Valerie; Harvey, Simon-Pierre; Vallerand, Robert J.
Abstract: Drawing from the dualistic model of passion for activities (Vallerand et al., 2003), this research investigated the role of passion for social partnered dancing in relationships quality with other dancers as well as outside of the dance community, in a romantic relationship. Study 1 showed that harmonious passion (HP) was related to enjoyment while dancing with a novice partner, whereas obsessive passion (OP) was associated with negative interactions with an incompetent partner. Study 2 showed that HP was positively related to relationship quality with a preferred dance partner and the dance community through mastery-approach and social connection goals, whereas the opposite effect characterized OP. Also, OP was negatively related to relationship quality with both a dance partner and a romantic partner through conflict, whereas the reverse trend characterized HP. This research identified mechanisms through which passion may affect relationships within and outside a passionate activity such as dance. Highlights: People can hold a harmonious (HP) and an obsessive passion (OP) for social dancing. HP and OP affect relationships both with dance partners and a romantic partner. HP fosters satisfying relationships through mastery and social connection goals. The reverse effects characterize OP. Passion also influences relationships through conflict between dance and romance.